2007
DOI: 10.1253/circj.71.1366
|View full text |Cite
|
Sign up to set email alerts
|

Renal Insufficiency is Related to Painless Myocardial Infarction

Abstract: ymptoms of acute myocardial infarction (MI) vary and may include painful symptoms, such as pain, pressure and tightness of the chest, and other atypical symptoms, such as dyspnea, lightheadedness, and nausea. Of these symptoms, painful symptoms are clinically most important because they encourage patients to seek immediate medical attention, leading to early diagnosis and early revascularization and thus improved prognoses. 1,2 However, MI can also occur without typical painful symptoms, 3,4 and in such cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The cause of this is thought to be the impairment of sensory and autonomic nerve functions seen in patients with renal failure. It was demonstrated in a study made by Komukai et al that as the renal function disorders increased, the prevalence of painless MI also increased (Komukai et al, 2007). In another study conducted by Pitsavos C et al, it was shown that MI patients with renal failure admitted to the hospital late and the possible reason for such late admission was thought to be the less occurence of alerting symptoms such as chest pain in this patient group (Pitsavos et al, 2007).…”
Section: Myocardiac Infarctionmentioning
confidence: 69%
“…The cause of this is thought to be the impairment of sensory and autonomic nerve functions seen in patients with renal failure. It was demonstrated in a study made by Komukai et al that as the renal function disorders increased, the prevalence of painless MI also increased (Komukai et al, 2007). In another study conducted by Pitsavos C et al, it was shown that MI patients with renal failure admitted to the hospital late and the possible reason for such late admission was thought to be the less occurence of alerting symptoms such as chest pain in this patient group (Pitsavos et al, 2007).…”
Section: Myocardiac Infarctionmentioning
confidence: 69%
“…Patients with chronic renal failure appear particularly disposed to silent ischemia. 11 In patients following myocardial infarction, 80-100% manifest silent ischemic episodes. 12 In patients with unstable angina, upwards of 90% have evidence of silent ischemia, 13 whereas in patients with sudden death, almost all are observed to have periods of silent myocardial ischemia.…”
Section: Definition and Prevalencementioning
confidence: 99%
“…Dyslipidemia was defined as serum total cholesterol concentration ≥220 mg/dl, serum high-density lipoprotein-cholesterol concentration ≤40 mg/dl, serum triglyceride concentration ≥150 mg/dl, or previous treatment. 7 Anemia was defined as a serum hemoglobin concentration on admission <11 g/dl. 8,9 Systolic dysfunction was defined as an ejection fraction on admission, estimated with echocardiography, of less than 50%.…”
mentioning
confidence: 99%